Encyclopedia of Life Sciences 2001
DOI: 10.1038/npg.els.0002101
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis

Abstract: Pneumocystis carinii is an opportunistic fungus which causes a type of pneumonia by proliferating extracellularly in the lung alveolus in immunodeficient mammalian hosts, such as patients with acquired immune deficiency syndrome and individuals undergoing immunosuppressive treatment for cancer or organ transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Recent studies with other respiratory pathogens (Yersinia pestis and Legionella pneumophila) have shown that they can invade and replicate in the type 1 pneumocyte cell line WI26 (Harb and Kwaik, 2000;Liu et al, 2006;Galvan et al, 2007). Moreover, Pneumocystis carini and Streptococcus pneumoniae have been shown to preferentially bind to and damage type I cells in vivo to achieve dissemination across the alveolar barrier (Nakamura and Wada, 1998;Kaneshiro, 2001;Garcia-Suarez Mdel et al, 2007). Preliminary studies in our lab confirmed that M. tb can invade and replicate in WI26 pneumocytes (Vir et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies with other respiratory pathogens (Yersinia pestis and Legionella pneumophila) have shown that they can invade and replicate in the type 1 pneumocyte cell line WI26 (Harb and Kwaik, 2000;Liu et al, 2006;Galvan et al, 2007). Moreover, Pneumocystis carini and Streptococcus pneumoniae have been shown to preferentially bind to and damage type I cells in vivo to achieve dissemination across the alveolar barrier (Nakamura and Wada, 1998;Kaneshiro, 2001;Garcia-Suarez Mdel et al, 2007). Preliminary studies in our lab confirmed that M. tb can invade and replicate in WI26 pneumocytes (Vir et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Pneumocystis pneumonia (PcP) remains a major opportunistic infection among AIDS patients and can also occur in those undergoing immunosuppressive treatment for cancer and solid organ transplantation (29,74). Pneumocystis is an unusual and ubiquitous fungal protist with several features unlike those of most other fungi (29,30).…”
mentioning
confidence: 99%
“…Pneumocystis is an unusual and ubiquitous fungal protist with several features unlike those of most other fungi (29,30). There is no adequate cultivation method yet developed that provides sufficient numbers of pure organism preparations suitable for many types of experiments.…”
mentioning
confidence: 99%
“…It has becoming evident that the high incidence of PcP in AIDS patients is global and that the organism can infect other immunodeficient people such as patients undergoing chemotherapy for cancer or solid organ transplant (1,2), children prior to becoming fully immunocompetent, and the elderly with diminished immune systems. Pneumocystis can also transiently colonize normal, healthy people and animals without causing overt symptoms of respiratory disorder.…”
mentioning
confidence: 99%